2022
DOI: 10.1111/all.15431
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of allergy and respiratory disorders in sport: An EAACI task force position paper

Abstract: Allergy and respiratory disorders are common in young athletic individuals. In the context of elite sport, it is essential to secure an accurate diagnosis in order to optimize health and performance. It is also important, however, to consider the potential impact or consequences of these disorders, in recreationally active individuals engaging in structured exercise and/or physical activity to maintain health and well-being across the lifespan. This EAACI Task Force was therefore established, to develop an up-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 130 publications
(220 reference statements)
0
9
0
Order By: Relevance
“…42,43 It is therefore often challenging to rule-out EIB in athletes with a mild or borderline response based on a solitary assessment 44 and thus repeat or "in-season" testing is recommended in this scenario. 12 Furthermore, a study by Bougault et al 42 evaluated EIB severity status in swimmers when they were in an intensive phase of training and out of training. The authors reported no changes in FeNO measurements, despite fluctuations in airway caliber in response to EVH and methacholine, which further supports the disconnect between FeNO and EIB in athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 It is therefore often challenging to rule-out EIB in athletes with a mild or borderline response based on a solitary assessment 44 and thus repeat or "in-season" testing is recommended in this scenario. 12 Furthermore, a study by Bougault et al 42 evaluated EIB severity status in swimmers when they were in an intensive phase of training and out of training. The authors reported no changes in FeNO measurements, despite fluctuations in airway caliber in response to EVH and methacholine, which further supports the disconnect between FeNO and EIB in athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise challenges are typically considered to provide the greatest specificity to detect EIB; however, EVH is thought to offer greater sensitivity 10,11 . Although indirect bronchial provocation challenges provide objective evidence of EIB, 12 they offer limited insight into inflammatory mechanisms or disease subtypes. Airway inflammation is thought to contribute to the development of EIB via release of potent bronchoconstrictive agents, such as mast cell‐derived prostaglandins, 13,14 and mast cell‐ and eosinophilic‐derived leukotrienes 14–16 …”
Section: Introductionmentioning
confidence: 99%
“…This environmental condition might very well be PM exposure. In addition, the recent position paper of European Academy of Allergy and Clinical Immunology highlights the importance of repeat assessment and requirement of in season testing 50…”
Section: Discussionmentioning
confidence: 99%
“…Elite athletes are more prone to develop asthma and the prevalence of asthma among athletes are higher when compared with the general population (1). Elite training is often considered to be a contributor to the development of asthma in athletes who did not exhibit respiratory symptoms before their sports careers (2).…”
Section: Introductionmentioning
confidence: 99%